(untitled) (Revista Peruana de Investigación Educativa, 2016)
This article is an ethnographic account of my experience as an enrolled student in one of the most popular private universities in Perú. I take special interest in describing the courses of personal education that occupy an important part of the curriculum in this institution. Based on Foucault’s theory of governmentality, I aim to analyze critically the content of these courses, the way they relate with the emergence of entrepreneurial subjects and its implications for citizenship formation.